Genially Interactive Media: Improving Learning Outcomes of Indonesian Cultural Wealth - Nurul Afni; Kurniana Bektiningsih (Journal of Education Reseach and Evaluation, 2024)
Education in Indonesia has shown progress in the last few decades. However, the education system in Indonesia still needs to overcome several challenges, especially in the context of teaching Natural and Social Sciences in Elementary Schools. This research aims to develop Genetically-based interactive media on Indonesian Cultural Wealth material in Natural and Social Sciences Subjects. This type of research is development research using the ADDIE model. The research subjects are learning materials experts and learning media experts. The test subjects were 19 class IV students and teachers. Data collection methods include observation, questionnaires, documentation, and tests. The data collection instrument uses a questionnaire sheet. Data analysis techniques use qualitative and quantitative descriptive analysis. N-gain is used to test media effectiveness. The validity test results show that genetically interactive media is very suitable for use. The use of this media also significantly improves student learning outcomes; student responses to the use of this media are also positive. Thus, Generative interactive media is effective and suitable for learning natural and social sciences in fourth-grade elementary school.